Construction Site Management and Labor Productivity Improvement : How to Improve the Bottom Line and Shorten the Project Schedule. - Thomas, H. Randolph, 1945- (American Society of Civil Engineers, 2017)
Thomas and Ellis provide detailed, straightforward management practices to improve construction site activity and reduce losses in labor productivity from the most common site challenges.
Keywords: Construction projects -- Management.; Project management.; Building -- Superintendence.; elektronické knihy; electronic books